(untitled) (Modern education and development, 2025)
This article examines lexical changes in modern Russian under the influence of internet communication. Based on the analysis of texts from the digital environment, typical models of neologism formation, their thematic groups, and frequency of use are identified. The study defines the main trends in updating the lexical composition of the 21st-century language. Quantitative and qualitative characteristics of new lexemes are presented, as well as their place in the language system discussed.